H-89 inhibits transient outward and inward rectifier potassium currents in isolated rat ventricular myocytes - Pearman, Charles (Nature Publishing Group, 2006)
1. Voltage clamp was used to investigate the effects of N-[2-p-bromo-cinnamylamino)ethyl]-5-isoquinolinesulfonamide (H-89), a potent inhibitor of PKA, on transient outward K(+) current (I(to)) and inward rectifying K(+) current (I(K1)) in rat cardiac muscle. 2. Initial experiments, performed using descending voltage ramps, showed that H-89 inhibited both the outward and inward ramp currents in a concentration-dependent manner at concentrations between 5 and 60 μmol l(−1). A similar degree of inhibition was observed when I(to) and I(K1) were recorded using square wave depolarising and hyperpolarising voltage steps, respectively. 3. The IC(50) was 35.8 μmol l(−1) for I(to) and 27.8 μmol l(−1) for I(K1) compared to 5.4 μmol l(−1) for L-type Ca(2+) current (I(Ca)). The Hill coefficients for I(to), I(K1) and I(Ca) were −1.97, −1.60 and −1.21, respectively. In addition to inhibiting I(to) amplitude, H-89 also accelerated the time to peak and the rate of voltage-dependent inactivation so that the time course of I(to) was abbreviated. 4. Paired-pulse protocols were performed to study the effects of H-89 on steady-state activation and inactivation as well as recovery from voltage-dependent inactivation. H-89 produced a concentration-dependent rightward shift in voltage-dependent activation but had no significant effect on steady-state inactivation. Recovery from voltage-dependent inactivation was delayed, although this was only visible at the highest concentration (60 μmol l(−1)) used. 5. In experiments investigating the effects of elevated cyclic AMP, the β-adrenergic agonist isoprenaline and the phosphatase inhibitor calyculin A had no major effects on I(to) or I(K1). 6. Data suggest that the effects of H-89 on K(+) currents are more complex than simple inhibition of PKA-mediated phosphorylation.